Remote Assessment of Post-Stroke Elbow Function Using Internet-Based Telerobotics: A Proof-of-Concept Study - Kim, Jonghyun; Sin, Minki; Kim, Won-Seok; Min, Yu-Sun; Kim, Woojin; Park, Daegeun; Paik, Nam-Jong; Cho, Kyujin; Park, Hyung-Soon (Frontiers in Neurology, 2020)
Purpose: Upper limb hemiparesis is the most common impairment in stroke survivors, and adequate assessment is crucial for setting the rehabilitation strategy and monitoring the effect of treatment. However, adequate timely assessments are difficult due to the limited accessibility to clinics for stroke survivors. We designed this study to investigate whether teleassessments for motor impairments of the spastic elbow (i.e., passive range of motion (PROM), muscle strength, and spasticity) are feasible in stroke survivors. Methods: To implement a telerobotic system for remote assessment with physical interaction, we constructed a system with a master robot interacting with a doctor (assessor) and a slave robot interacting with the elbow of a subject with stroke. The master robot is operated by the doctor, where the torque and the speed are transferred to the slave robot via the internet, and the reaction of the patient’s elbow to the slave robot’s movement is measured with a torque sensor, then finally transferred back to the master robot. An intercontinental remote assessment, which is considered one of the worst possible scenarios, was used as a clinical test to strictly check the feasibility. For the clinical tests, the examiner for the teleassessment was located at a lab in the National Institutes of Health (NIH, Bethesda, MD, USA) while the stroke patients were located at Seoul National University Bundang Hospital (Bundang, Kyeonggido, South Korea). Results: In total, 12 stroke patients’ elbows (age range: 28 - 74, M:F=6:6) were tested. For the PROM, the absolute difference between two assessments (in-person versus remote) was 5.98±3.51 degrees on average (range: 0 – 11.2). The agreements for the strength and the spasticity of elbow flexor between in-person and remote assessments were substantial (k=0.643) and fair (k=0.308), respectively. No adverse events were observed during or immediately after the telerobotic assessment. Conclusions: Internet-based telerobotic remote assessment for motor impairment of spastic elbow in stroke using our system is feasible even in the worst setting, with too long of a distance and a delayed communication network.